Speed Control of Permanent Magnet Synchronous Motor Based on Variable Fractional-Order Fuzzy Sliding Mode Controller - Liping Chen; Haoyu Liu; Ze Cao; António M. Lopes; Lisheng Yin; Guoquan Liu; Yangquan Chen (Actuators)
A variable fractional-order (VFO) fuzzy sliding mode controller is designed to control the speed of a permanent magnet synchronous motor (PMSM). First, a VFO sliding mode surface is established. Then, a VFO fuzzy sliding mode controller is designed, capable of suppressing the effects of parameter uncertainties and disturbances to achieve precise PMSM speed control. The global stability and finite time convergence of the controlled system state are demonstrated using Lyapunov stability theory. The numerical and experimental results validate the effectiveness of the controller, showing better immunity to disturbances and a smaller overshoot compared to PID and fixed-order fuzzy sliding mode controllers.